Brand Image, Price Perception, and Their Impact on Consumer Purchase Intention in Culinary MSMEs - Marliana Hulu; Ahmad Johan; Adi Praptika (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of brand image and price perception on consumer purchase intention in the culinary MSME sector. A quantitative approach with descriptive and verificative methods was employed. Data were collected through questionnaires distributed to 126 consumers selected using purposive sampling. The analysis involved validity and reliability testing, classical assumption tests, multiple linear regression, and hypothesis testing. The findings indicate that brand image has a positive and significant effect on purchase intention (t = 5.565, p < 0.001), while price perception demonstrates a stronger positive influence (t = 7.423, p < 0.001). Simultaneously, both variables significantly affect purchase intention and explain 92% of its variance (F = 709.8; R² = 0.920). These results imply that strengthening brand credibility and implementing appropriate pricing strategies are essential for increasing consumer purchase intention and enhancing the competitiveness of culinary MSMEs.